PENGENALAN AKUNTANSI HUTANG BAGI SISWA/I SMA PROVIDENTIA - Yanti; Callista, Lauren; Dintia, Cecillia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
Based on the results of interviews with accounting teachers, there is a problem where when the school sends its students to accounting competitions outside of school, the students often experience difficulty in answering questions, especially in calculating single interest and compound interest contained in debt material. This is because students at SMA Providentia have never been taught about debt at school. For this reason, we from the PKM Team will provide a solution to this problem by providing training on liability accounting. Training is carried out over five meetings in extracurricular subjects with a duration of 60 minutes per meeting, once a week. The training participants were 6 class XII students majoring in Social Sciences. PKM is carried out using lecture methods, discussions, discussing practice questions and giving quizzes as feedback. The conclusions from this training are: the school is quite cooperative in providing the infrastructure needed for PKM activities, students are quite enthusiastic and have good interactions in taking part in the training, the results of the quiz given show that after the training is given, students can understand the material well debt given, and based on the answers to the questionnaire, all training participants gave a satisfactory general impression of this training. The two outputs produced in this PKM are publications in the Serina Abdimas Journal as mandatory outputs and HKI in the form of Patents as additional outputs.